Kearifan Lokal Tembang Macapat Masyarakat Karang Baru, Sriwijaya, Kecamatan Sumbersari, Kabupaten Jember. - Anista, Yuni; Jayanti, Maulia Fitri; Nurhayati, Alfisyah (CV. ITTC INDONESIA, 2023)
The aim of this research is to examine and record regional knowledge that still exists among the people of Karang Baru, Sriwijaya, Sumbersari District, and Jember Regency as Tembang Macapat. Tembang Macapat is an ancient Javanese oral literary tradition that embodies local wisdom that is closely related to cultural values, ethics and traditional knowledge. The research technique used is qualitative research, namely conducting interviews with members of the local community who have high knowledge about Tembang Macapat. Research findings show that Tembang Macapat is currently getting worse and is starting to disappear from the daily lives of the people of Karang Baru. Macapat songs are performed at various events, ranging from religious ceremonies, traditional celebrations, to providing moral lessons to the younger generation. This research offers a deeper understanding of the value of local wisdom expressed in macapat songs as a component of the cultural identity of the Karang Baru community. The community is expected to be able to maintain cultural heritage and local wisdom as valuable assets in facing changing times through preserving and developing these traditions.